The Influence of the School Environment on Student Character from the Perspectives of Teachers, Students and Parents - Nurzanah, Luthfi Fitriani; Yuliyanto, Aan; Sofiasyari, Irma; Hidayati, Novi; Ruslianti, Destian; Rosliawati, Lia (International Conference on Elementary Education, 2024)
In the era of modern education, not only academic knowledge is considered necessary, but also the formation of strong character in students, especially in terms of empathy. Many things can influence character, one of which is the school environment. The school environment greatly influences student character. If the school environment is favourable, positive character will be formed, and conversely, if the environment is hostile, the student's character will become less suitable. This literature review will discuss the influence of the school environment on students' empathetic character, which will later be reviewed from the perspective of teachers, students and parents. The responses or perspectives of students, teachers and parents are used as an indicator for research. The student's perspective is seen from social interactions in the school environment, the teacher's perspective is seen from the teacher's assessment of student behaviour, and the parent's perspective is seen from open communication regarding the character of Empathyempathythis literature review and the three subject perspectives, it can be concluded that the school environment is the second place for forming students' empathetic character, and the school environment is very influential in forming students' character.